Building a Local Arbitration System: An Alternative for Civil Dispute Resolution in Wameo, Indonesia - Ashadi L. Diab; Muhammad Restu Al Lail; Fitri Fua (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Arbitration represents a mechanism for alternative civil dispute resolution outside the general judicial system, producing decisions that are final and binding upon the parties involved. Objectives: This study aimed to analyze the effectiveness of arbitration as an alternative dispute resolution mechanism in Baubau City, Southeast Sulawesi, considering both legal frameworks and local socioeconomic conditions, while identifying factors that influence its implementation at the regional level. Method: A descriptive qualitative approach was employed, with data gathered through literature review, field observation, and informal interviews with business actors and legal practitioners in Baubau City. Result: Results revealed that arbitration possesses notable advantages including time efficiency, procedural flexibility, and confidentiality guarantees. However, its implementation in Baubau City continues to face significant barriers: low legal literacy among community members, limited access to arbitration institutions, the absence of a local arbitration body, and minimal socialization efforts regarding arbitration procedures. Consequently, the community predominantly relies on informal deliberation (musyawarah) or court litigation as dispute resolution mechanisms. Conclusion: The effectiveness of arbitration in Baubau City remains suboptimal, attributable not to normative regulatory weaknesses but rather to infrastructural deficiencies and insufficient public understanding. Strategic initiatives are therefore required, encompassing institutional strengthening of arbitration at the local level and enhanced legal education and community outreach. These efforts are expected to promote arbitration as a more effective and accessible alternative dispute resolution mechanism at the regional level. Keywords: arbitration system, local arbitration, civil dispute resolution, alternative dispute resolution, Baubau City